EFEKTIFITAS PENERAPAN PERATURAN PEMERINTAH NOMOR 24 TAHUN 2018 TENTANG PELAYANAN PERIZINAN BERUSAHA TERINTEGRASI SECARA ELEKTRONIK PADA PELAYANAN TERPADU SATU PINTU KABUPATEN BANTAENG - Masturi, Rahmad; Kamran, Muhammad; Nugraha, A Afgan; Adabi, Muhammad Ikhwan (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2024)
The efficiency with which Government Regulation Number 24 of 2018 is being implemented in the area of electronically integrated business licensing. The study's goals are as follows: (1).Explain how Government Regulation Number 24 of 2018 in Electronically Integrated Business Licensing (2) is applied and analyze it. The aim of this study is to examine and elucidate the challenges encountered during the execution of Government Regulation Number 24 of 2018 concerning Electronically Integrated Business Licensing. Normative research is the analytical technique employed, which entails gathering data via a review of the literature. The study's findings indicate that the electronic one-stop integrated service policy has not been fully implemented effectively. This is because of a number of factors, the first of which is the occurrence of network disruptions during system operation. These disruptions can make it more difficult for the integrated licensing service information system to perform its functions, including data collection, printing, and monitoring. Thus, network interruption is a critical component in the deployment of an integrated licensing service information system, according to experts. The second issue is a lack of management training, which can lead to a lack of understanding among staff members and impede work processes. Third, there are still people who visit the office to take care of permits because there is a deficiency of socialization in the neighborhood.It is anticipated that the government's electronic one-stop integrated service program will be further enhanced in order to ensure smooth operation free from any roadblocks that could impede the system's implementation.